An Archaeological Site on Karluk Island in Crozier Strait, N.W.T. - Ruffman, Alan (ARCTIC, 1976)
During a marine geophysical exploration, in 1973, of the proposed route of a gas pipeline across Crozier Strait (between Bathurst Island and Little Cornwallis Island) in the Canadian Arctic Archipelago, the present author landed on the western side of Karluk Island, which is situated in the narrowest part of the Strait. There, conspicuous on a small point facing south and west, and directly west of a small lake, he noticed a newly-erected small cairn of a lead-zinc claim which led him inadvertently to the discovery of an archaeological site. Three or four depressions, each not more than 30 cm deep and filled with a thick, spongy, brilliant green moss, stood out in contrast to the surrounding brown rock rubble. .